Assessment of the economic development of Latvia and Ukraine - Skribane, Irina; Broyaka, Antonina (University of Latvia, 2020)
The global financial crisis and the ensuing global recession not only adversely affected global growth and poverty, but also presented constraints and challenges to public policy. Even though the world economy is slowly returning to growth, the recovery was difficult and lasted for almost 10 years. Preparing for the future requires an assessment of the consequences of the crisis and future challenges. Since 2010 economic growth in Latvia has been one of the fastest in the EU (from 2011-2018, GDP, on average, increased by 3.5% annually), however in 2019 economic growth has moderated. Growth opportunities are limited both by the uncertainty in the external environment (“trade wars” on the global economy, the outcome of Brexit, slower growth in EU countries, etc.), and the existing economic structure, which also negatively affects the competitiveness of Latvian producers. In the competitiveness rankings regularly published by the World Economic Forum (WEF), Latvia lags far behind other new EU member states, incl. other Baltic States. The economy of Ukraine currently is in very difficult environment: carrying out the Anti-terrorism activity in the eastern part, occupation of Crimea, the uncertainty in the system of political processes, the economic instability and other factors slow down its development. The deepening of the political and economic crisis in Ukraine, on the one hand, and transformational processes towards expanding European integration, on the other hand, daily create new challenges that domestic economic entities have not encountered before, and which are difficult to predict. The aim of the research is to carry out a comprehensive assessment of the dynamics of macroeconomic indicators of the social and economic development of the national economies of Latvia and Ukraine over the past 10 years (from 2010 to 2019) and identify the factors influencing it, to improve the forecasting of further trends and the planning of anti-crisis measures. As a result of the study, possible directions of economic policy were identified to improve the economic structure of Latvia and Ukraine in order to promote their sustainable development and competitiveness in the world market.
Keywords: economics development; GDP growth; competitiveness; Latvia; Ukraine; Research Subject Categories::SOCIAL SCIENCES::Business and economics